On the solutions of nonlinear third order boundary value problems - Smirnov, Sergey (Mathematical Modelling and Analysis, 2010)
The author considers a three‐point third order boundary value problem. Properties and the structure of solutions of the third order equation are discussed. Also, a connection between the number of solutions of the boundary value problem and the structure of solutions of the equation is established. First published online: 09 Jun 2011